Expression analysis of acdS-gene of Pseudomonas putida B-37 in transgenic plants Nicotiana tabacum - Melnikava, Alesia A.; Khramtsova, Alena A.; Karaleva, Katsiaryna S.; Rutkevich, Daria A.; Kukulianskaya, Tatsiana A. (Experimental Biology and Biotechnology, 2019)
In current work was realized the transfer of recombinant plasmid pBI121acdS, carring P. putida B-37 bacterial acdSgene to the A. tumefaciens AGL0 cells. Transgenic plants of N. tabacum were created by agrobacterial transformation. Integration of P. putida B-37 bacterial acdS-gene to transgenic plants of N. tabacum was verified by PCR analysis, using specific primers to present gene. Presence of target acdS-gene in transgenic plants genome was proved by RT-PCR analysis. With help of  Real-time PCR was shown the difference between reference gene and target P. putida B-37 bacterial acdSgene expression. Expression of target gene exceeded reference gene in 1.27 times, those fact proved expression of acdS-gene in plants on high level. Expression of the heterologous gene in N. tabacum plants was also proved by biochemical method of ACC-deaminase specific activity define.
Keywords: ACC-deaminase; Nicotiana tabacum; acdS-gene; Pseudomonas putida